Predictors of Difficult Laparoscopic Appendectomy in Acute Appendicitis - Karki, Mukesh; Belbase, Narayan (Journal of College of Medical Sciences-Nepal, 2021)
Introduction Acute appendicitis is the most common surgical emergency of the abdomen and appendectomy is one of the most frequently performed surgical procedures. Laparoscopic appendectomy is one of the commonest surgical procedure in most of the tertiary center and is being an effective alternative to open appendectomy. Despite continuing evolution in laparoscopic appendectomy, this procedure continue to carry the risk of conversion to open appendectomy. The objective was to analyze the factor, identify the predictors for difficult laparoscopic appendectomy. Methods The study was conducted in College of Medical Sciences, Bharatpur. All patients who underwent laparoscopic appendectomy from 1st January 2020 to 30th December 2020 were included in the study after taking written informed consent. A detailed performa was developed to record information regarding patient history, physical examination, laboratory parameters, ultrasonography findings, CT findings and intra-operative details. Laparoscopic appendectomy done in more than 120 minutes, converted into open due to difficulty in surgery and not due to complications, severe adhesions were considered to be a case of difficult appendectomy. Results In our study total 94 patients underwent laparoscopic appendectomy among which 16 (17.02%) cases had difficult appendectomy. The incidence of difficult appendectomy was higher among older age group, male sex, long duration of symptoms, high white blood cell count, difficult anatomy, pre existing co-morbid condition, extreme findings on computed tomography and ultrasonography (USG). Operating time, anaesthetic time, and duration of hospital stay were longer after difficult appendectomy. Conclusions Identifying the potential factors for conversion preoperatively may assist the surgeons in making decisions concerning the management of patients with appendicitis and in the judicious use of laparoscopic appendectomy. From our study we found that independent predictors for difficult appendectomy are old age, male sex, prolonged duration of symptoms, high white blood cell count, higher body mass index (BMI), extreme inflammation in computed tomography scan and ultrasonography. Proceeding directly with open appendectomy under these circumstances may reduce operative time, reduce hospital stay and morbidity. Keywords: Acute appendicitis, Laparoscopic appendectomy, Open appendectomy, Conversion